Complex Constellation of Gastroptosis, Achalasia, and Hypertophic Gastritis: A Case Report - Elvina Prisila; Rheycado Arrafi Pratama; Novi Wijayanti Sukirto; Salsabila Chairunnisa Ramadhani (Jurnal Impresi Indonesia, 2025)
The concurrent presentation of multiple upper gastrointestinal (GI) disorders is a rare clinical entity that poses significant diagnostic and therapeutic challenges. We present an unprecedented case of coexisting achalasia, gastroptosis, hypertrophic gastritis, and hyperacidity, which culminated in a life-threatening metabolic emergency. Case presentation: A 63-year-old female with a history of chronic dyspepsia presented with progressive nausea, vomiting, significant weight loss, and an acute episode of severe hypoglycemia (random blood glucose 52 mg/dL). A barium contrast study (Oesophagus-Maag-Duodenum) was the key diagnostic investigation. Radiological findings revealed a dilated esophagus with a distal "rat tail" sign characteristic of achalasia. The same study demonstrated severe inferior displacement of the stomach into the pelvic cavity, confirming gastroptosis, and markedly thickened gastric mucosal folds, indicative of hypertrophic gastritis. Conclusion: This case illustrates a unique constellation of anatomical, motor, and inflammatory GI pathologies. The severe hypoglycemia is attributed to a "double-delay" mechanism, where esophageal stasis from achalasia combined with delayed gastric emptying from gastroptosis led to erratic nutrient delivery and a dysregulated, exaggerated insulin response. This report highlights the critical role of comprehensive radiological evaluation in diagnosing complex, overlapping GI conditions and underscores the importance of considering multi-pathology interplay when faced with atypical clinical manifestations.